Graphene oxide beads for fast clean-up of hazardous chemicals. Issue 24 (1st June 2016) - Bao, Chenlu; Bi, Shuguang; Zhang, He; Zhao, Jinliang; Wang, Pengfei; Yue, Chee Yoon; Yang, Jinglei
Abstract : Graphene oxide beads have core/shell structures and are good absorbers of various chemicals. Abstract : Spills or leakages of hazardous chemicals involve high safety, health and environmental risks. Absorption of hazardous chemicals using absorbent materials is an advanced and efficient strategy for cleaning up hazardous chemical spills. Here, we report a new form of carbon-based macrostructure, graphene oxide beads with core/shell structures, for fast clean-up of hazardous chemicals. Graphene oxide beads are produced by one-step self-assembly of graphene oxide in a coagulation bath. The core of the beads is graphene oxide foam, while the shell is a graphene oxide membrane. The amphipathic and porous core provides a large absorption capacity for a broad range of hazardous chemicals. By incorporating layered silicates, graphene oxide beads become highly fire retardant, hence are especially suitable for cleaning up chemicals with accompanying fire risks. The millimeter-level size and spherical morphology of the beads offer high convenience in practical usage. Moreover, the beads can also be used in many other applications, such as heat energy storage and sustained release.